Serum Sphingolipids Aiding the Diagnosis of Adult HIV-Negative Patients with Talaromyces marneffei Infection - Li, Zheng-Tu; Yau, Lee-Fong; Qiu, Ye; Li, Shao-Qiang; Zhan, Yang-Qing; Chan, Wai-Him; Chen, Zhao-Ming; Li, Zhun; Li, Yongming; Lin, Ye; Cheng, Jing; Zhang, Jian-Quan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Increasing attention has been directed to Talaromyces marneffei (T. marneffei) infection in HIV-negative patients due to its high mortality rate. However, nonspecific symptoms and biological characteristics similar to those of other common pathogenic fungi complicate the rapid and accurate diagnosis of T. marneffei infection. Sphingolipids (SPLs) are bioactive lipids involved in the regulation of various physiological and pathological processes and have been identified as serum biomarkers for several diseases. This study employed a sphingolipidomic approach established in our previous work to explore the use of serum SPLs in the diagnosis of HIV-negative patients with T. marneffei infection. Additional clinical cohorts of patients infected with other microorganisms were also recruited. We found that sphinganine (Sa) (d16:0) exhibited obvious depletion after infection; moreover, its level in patients with T. marneffei infection was significantly lower than that in patients infected with other microorganisms. Therefore, Sa (d16:0) was considered a specific diagnostic biomarker for T. marneffei infection, and 302.71 nM was selected as the optimal cutoff value with a diagnostic sensitivity of 87.5% and specificity of 100%. These results suggested that determination of serum Sa (d16:0) levels can be used as a new alternative tool for the rapid diagnosis of T. marneffei infection in HIV-negative patients.